Assessing the institutions-innovation channel within the inequality-growth nexus - Yang Sun; Joshy Z. Easaw; Vassilis Logothetis (Cardiff University, Cardiff Business School, 2023)
The present paper assesses the interactions between innovation and economic institutions within the context of the inequality-growth nexus. By carrying out fixed effects estimations on a cross-country panel, we find that both institutional quality and innovations improve economic growth at the expense of income equality. We show that the marginal effects of innovations on growth and inequality diminish as institutions increase in quality, and the effects of institutions can be influenced by level of innovations. This indicates that while institutions and innovations can be inequality-inducing, their interactions dampen the effect. Similarly, both variables positively affect growth but their interactions are negative. More importantly, we note a series of transitory interactive effects on growth which show property right protection as the principal growth-enhancing institutions in earlier stages of development, and broader institutional quality in later stages. These results are verified and reinforced by GMM and IV estimations, the latter of which uses judicial independence as an instrument, as well as additional robustness tests.
Keywords: C33; C36; D63; O33; O34; O43; O47; 330; income inequality; economic growth; institutions; entrepreneurship; innovation